Subcortical crossed aphasia- A clinical case report - Ranjitha Kashyap B Na, Anju Sara Ebya, Brenda Jane Pereiraa, Kajol N a, Abhishek B P (Journal of All India Institute of Speech and Hearing, 1970)
A 42- year old woman, right hander, underwent ow diverter placement surgery for right ophthalmic ICA aneurysm cure following which she sueredwith acute subcortical crossed aphasia, left upper and lower limb paralysis. There was an intra-parenchymal hemorrhage with hematoma in right external capsule, putamen, coronaradiata, a part of the centrum semiovale and perilisional edema in the posterior internal capsule post surgery. The patient's language pro le was characterized by marked word nding diculty. Spontaneous speech had perseverative and paraphasic errors, phonemic substitutions, hesitations and groping.